Identification and functional analysis of genetic variants of ISL1 gene promoter in human atrial septal defects. (27th October 2022) - Yin, Xiu‐Yun; Chen, Huan‐Xin; Chen, Zhuo; Yang, Qin; Han, Jun; He, Guo‐Wei
Abstract: Background: Atrial septal defect (ASD) is a common type of congenital heart disease. A gene promoter plays pivotal role in the disease development. This study was designed to investigate the pathological role of variants of the ISL1 gene promoter region in ASD patients. Methods: Total DNA extracted from 625 subjects, including 332 ASD patients and 293 healthy controls, was sequenced to identify variants in the promoter region of ISL1 gene. Further functional analyses of the variants were performed with dual luciferase reporter assay and electrophoretic mobility shift assay (EMSA). All possible binding sites of transcription factor affected by the identified variants were predicted using the JASPAR database. Results: Four variants in the ISL1 gene promoter were found only in patients with ASD by sequencing. Three of the four variants [g.4923 G > C (rs541081886), g.5079 A > G (rs1371835943) and g.5309 G > A (rs116222082)] significantly decreased the transcriptional activities compared with the wild‐type ISL1 gene promoter ( p  < 0.05). The EMSA revealed that these variants [g.4923 G > C (rs541081886), g.5079 A > G (rs1371835943) and g.5309 G > A (rs116222082)] in the ISL1 gene promoter affected the number and affinity of binding sites of transcription factors. Further analysis with the online JASPAR database demonstrated that a cluster of putative binding sites for transcription factors may be altered by these variants. Conclusions: These sequence variants identified from the promoter region of ISL1 gene in ASD patients are probably involved in the development of ASD by affecting the transcriptional activity and altering ISL1 levels. Therefore, these findings may provide new insights into the molecular etiology and potential therapeutic strategy of ASD. Abstract : This study investigated the pathological role of variants of ISL1 gene promoter region in a common type of congenital heart disease‐atrial septal defect (ASD) by sequencing DNA extracted from 625 subjects, including 332 ASD patients and 293 healthy controls. Four variants in ISL1 gene promoter were found only in patients with ASD and in further functional analyses three of those [g.4923 G>C (rs541081886), g.5079 A>G (rs1371835943), g.5309 G>A (rs116222082)] significantly decreased the transcriptional activities and affected the number and affinity of binding sites of transcription factors. These findings provide new insights into the molecular etiology and potential therapeutic strategy of ASD.